Kajian terhadap watak :peranan impressionism dan surrealism dalam pembinaan psikologi watak - Jaffar, F. (University Malaysia Sarawak, UNIMAS., 2007)
This research focused on the role of Impressionism and Surrealism to develop character psycholoies. Impressionism and Surrealism are directing stylistic steam which contributes enormous in filming world. Both of these styles are used by the director to apply emotion, feelings, pain, suffering, happiness, dream and other aspect of emotion based on the character in the film. The existences of these elements make characters more strong after combined it with interesting plot.